2010
DOI: 10.1111/j.1365-2869.2009.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances as a predictor of occupational injuries among public sector workers

Abstract: SUMMAR Y The association between disturbed sleep and increased risk of occupational injury has been observed in several cross-sectional and case-control studies, but prospective evidence is lacking. We examined prospectively whether sleep disturbances predicted occupational injuries in a large population of Finnish public sector employees. A total of 48 598 employees working in 10 municipalities and 21 hospitals in various parts of Finland were included. Sleep disturbances were assessed with the four-item Jenk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 21 publications
5
73
2
Order By: Relevance
“…It consists of 4 items on a 6-point rating scale (1=never to 6=almost every night). The respon- dents were classified as having a sleep disturbance when they reported any of the 4 problems for most of the nights (5-7 nights per week) (22). Sleep disturbance was assessed at baseline and 12 and 52 weeks.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…It consists of 4 items on a 6-point rating scale (1=never to 6=almost every night). The respon- dents were classified as having a sleep disturbance when they reported any of the 4 problems for most of the nights (5-7 nights per week) (22). Sleep disturbance was assessed at baseline and 12 and 52 weeks.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…As for personal factors, female gender 13,14) and younger age (<25 yr 15,16) , <30 yr [17][18][19] ) or older age (≥40 17) ) have been reported as risk factors. Health-related risk factors such as obesity 20) , sleep disorders 18,21,22) and smoking habit 8,18,21) are also indicated. Work related factors are known to be risk factors as well.…”
Section: Introductionmentioning
confidence: 99%
“…In the cited study, disturbed sleep was defined as responding "Yes" to the question "Have you had difficulty sleeping during the last two weeks". Salminen et al (35) conducted a largescale prospective study among public sector workers and found that difficulty initiating sleep was a predictor of occupational accidents with sick leave among women during the following year (OR 1.69, 95% CI 1.26-2.26). However, in contrast to the present study, changes in the occurrence of sleep disturbance during the follow-up period were not taken into account, making the role of the persistence of the sleep disturbance unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The few prospective studies within this field are limited by not being population based (35) or only including fatal accidents (36). Furthermore, to our knowledge, no studies have previously focused on sleep disturbances and work injuries solely among women.…”
mentioning
confidence: 99%